THE 2023 UNITED STATES–IRAQ CONFLICT REVIEWED FROM THE PERSPECTIVES OF LEADERSHIP AND STRUGGLE, AND ITS IMPLICATIONS FOR THE INDONESIAN NAVY - Yusuf Muchram Pribadi; Widarta Kusuma; Hendro Wijiantoro (AGUSPATI Research Institute, 2026)
The 2003 United States invasion of Iraq stands as one of the most controversial military interventions of the early twenty-first century. This study examines the conflict from the perspectives of leadership, fighting spirit, international humanitarian law, and its strategic lessons for the Indonesian Navy. Using a qualitative method, the research analyzes the historical background of the war, the legal and political justifications advanced by the United States, the collapse of Saddam Hussein’s regime, and the prolonged instability that followed the invasion. The findings show that the conflict reflected a sharp contrast between George W. Bush’s preemptive and decisive leadership style and Saddam Hussein’s authoritarian-personalistic rule, both of which revealed critical weaknesses in long-term strategic governance. The study also highlights that military superiority and rapid tactical victory did not guarantee strategic success, particularly in the absence of effective post-conflict planning, institutional reconstruction, and public legitimacy. Furthermore, the conflict demonstrated serious humanitarian consequences, including civilian casualties, torture, sectarian violence, and mass displacement. For the Indonesian Navy, the Iraq War offers important lessons regarding comprehensive strategic planning, operational adaptability, technological readiness, intelligence accuracy, and the necessity of upholding humanitarian values in modern military operations.